2016
DOI: 10.1016/j.cmi.2015.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Bloodstream infection caused by extensively drug-resistant Acinetobacter baumannii in cancer patients: high mortality associated with delayed treatment rather than with the degree of neutropenia

Abstract: This study aimed to describe severe infections with extensively drug-resistant Acinetobacter baumannii-calcoaceticus complex (XDR-ABC), as well as to investigate risk factors for mortality, in cancer patients. It was a retrospective study including all patients diagnosed with XDR-ABC bacteraemia during hospitalization in the intensive care unit of a cancer hospital between July 2009 and July 2013. Surveillance cultures were collected weekly during the study period, and clonality was analysed using pulsed field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(68 citation statements)
references
References 28 publications
3
62
0
3
Order By: Relevance
“…Previous studies have demonstrated that crude mortality rates in patients with AB bacteremia varied between 30 and 76%, and factors associated with worse prognosis include immunosuppression (Gulen et al, 2015; Townsend et al, 2015; Gu et al, 2016), drug resistance (Lee et al, 2007; Sunenshine et al, 2007; Fu et al, 2015; Guo et al, 2016), severity of underlying illness (Seifert et al, 1995; Chopra et al, 2013, 2014; Nutman et al, 2014), inappropriate antimicrobial therapy (Esterly et al, 2011; Huang et al, 2012; Shorr et al, 2014; Freire et al, 2016), septicemia (Huang et al, 2012; Ñamendys-Silva et al, 2015; Freire et al, 2016), and prior antibiotic exposure (Chopra et al, 2013, 2014; Gu et al, 2016; Liu et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that crude mortality rates in patients with AB bacteremia varied between 30 and 76%, and factors associated with worse prognosis include immunosuppression (Gulen et al, 2015; Townsend et al, 2015; Gu et al, 2016), drug resistance (Lee et al, 2007; Sunenshine et al, 2007; Fu et al, 2015; Guo et al, 2016), severity of underlying illness (Seifert et al, 1995; Chopra et al, 2013, 2014; Nutman et al, 2014), inappropriate antimicrobial therapy (Esterly et al, 2011; Huang et al, 2012; Shorr et al, 2014; Freire et al, 2016), septicemia (Huang et al, 2012; Ñamendys-Silva et al, 2015; Freire et al, 2016), and prior antibiotic exposure (Chopra et al, 2013, 2014; Gu et al, 2016; Liu et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…The hallmark of the XDR phenotype is carbapenem resistance. CRAB strains tend to be XDR-that is, resistant to all other antibiotics, with the exception of polymyxins, tigecycline, and sometimes aminoglycosides (50,52,53). NHSN and Eurofins surveillance data highlight that carbapenem resistance occurs in more than 50% of A. baumannii ICU isolates in the United States, by far the highest rate of resistance for any pathogen surveyed (27,181,182).…”
Section: Antibiotic Resistance Drives Outcomesmentioning
confidence: 99%
“…To circumvent the intrinsic resistance of many mouse strains to A. baumannii infection, artificial models have been used, such as infecting mice intraperitoneally (a clinically irrelevant route of entry) or mixing the inoculum with porcine mucin as a foreign body that inhibits the host's immune system from rapidly clearing the organism (59,60). In addition, mice are often made neutropenic prior to infection even though neutropenia is not a common risk factor for infections caused by A. baumannii, and the vast majority of patients infected with A. baumannii have neither deficiency in leukocyte numbers nor overt defects in leukocyte function (25,(50)(51)(52)(53)(61)(62)(63)(64)(65)(66)(67)(68). Results from such models must be interpreted circumspectly given the unclear applicability to clinical disease.…”
Section: Models Of Infectionmentioning
confidence: 99%
“…In the later period, such patients were less frequent and the number of central line infections was more common. Bacteremic pneumonia is one of the most fatal types of bacterial infection [17], whereas central line infection can be controlled relatively easily with early removal of infected devices [18]. In this study, central line infection was independently associated with 14-day survival.…”
Section: Discussionmentioning
confidence: 57%